2019
DOI: 10.18321/ectj794
|View full text |Cite
|
Sign up to set email alerts
|

Silica from Kazakhstan Rice Husk as an Anode Material for LIBs

Abstract: This paper reports the synthesis of the silica (SiO2) from Kyzylorda rice husk (RH) and investigation of its electrochemical behaviour as an anode material for the lithium-ion battery. Rice husk, considered as agricultural waste material, contains a substantial amount of amorphous silica, carbon, and minor other mineral composition, which have potential industrial and scientific applications. Due to the high theoretical capacity of silicon (4200 mAh g-1) and silicon dioxide (1965 mAh g-1), Si-containing compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
5
0
4
Order By: Relevance
“…The endothermic process occurs at an early stage, corresponding to the loss of water in the sample (~ 7.4%). In the second stage, a reaction with KOH consisting of C/SiO 2 , includes a reaction between KOH and SiO 2 according to the equation (1) which was early reported by Kurmanbayeva et al 16 Meanwhile, the reaction between KOH and carbon can also occur following the reaction mechanism proposed by J Romanos et al 17 at conditions below 700°C (shown as equations 2, 3, 4, 5). Consequently, the product formed from this process includes H 2 O, H 2 , K 2 CO 3 .…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The endothermic process occurs at an early stage, corresponding to the loss of water in the sample (~ 7.4%). In the second stage, a reaction with KOH consisting of C/SiO 2 , includes a reaction between KOH and SiO 2 according to the equation (1) which was early reported by Kurmanbayeva et al 16 Meanwhile, the reaction between KOH and carbon can also occur following the reaction mechanism proposed by J Romanos et al 17 at conditions below 700°C (shown as equations 2, 3, 4, 5). Consequently, the product formed from this process includes H 2 O, H 2 , K 2 CO 3 .…”
Section: Resultsmentioning
confidence: 91%
“…TGA curve of the C/SiO 2 material shows two stages of weight loss at $100 C and $300 C. The endothermic process occurs at an early stage, corresponding to the loss of water in the sample ($ 7.4%). In the second stage, a reaction with KOH consisting of C/SiO 2 , includes a reaction between KOH and SiO 2 according to the equation ( 1) which was early reported by Kurmanbayeva et al 16 Meanwhile, the reaction between KOH and carbon can also occur…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Однако наноструктурированные Si материалы также сталкиваются с некоторыми серьезными проблемами, сопровождающимися высокой площадью поверхности и отношением поверхности к объему, включая ограничение необратимой емкости и низкую кулоновскую эффективность, которые вызваны образованием пассивирующего слоя или слоя раздела твердого электролита на поверхности электрода [41]. В работах [42][43][44] в композитной системе кремниевые материалы действуют как активные компоненты, способствующие высокой емкости накопления лития, в то время как углеродная матрица может значительно сдерживать объемное расширение Si, улучшать электронную проводимость и стабилизировать межфазные слои из твердого электролита анодов на основе Si.…”
Section: литиевые источники токаunclassified
“…As a result, it is possible to separate the stages of drying [19], pyrolysis and oxidation of fuel [20,21] along the length of the reactor. Different thermal structures of the combustion wave provide localization of each substance in specific zones according to their physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%